2012
DOI: 10.1373/clinchem.2011.170464
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serum Creatinine and Cystatin C for Early Diagnosis of Contrast-Induced Nephropathy after Coronary Angiography and Interventions

Abstract: BACKGROUND:The diagnostic accuracy of serum creatinine and cystatin C (Cys) as early predictors of contrast-induced nephropathy (CIN) has been debated. We investigated the diagnostic sensitivities, diagnostic specificities, and variations from baseline for serum creatinine and Cys in CIN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 32 publications
9
53
0
Order By: Relevance
“…In present study was found a highly significant increment in serum creatinine and cystatin C while decrease in eGFR 24 hours after angiography (p<0.001, 0.01) when compared between two groups (CIN+, CIN-). This result is consistent with Wang et al, Liu et al and Nozue et al founded serum level of cystatin C is a reliable marker for CIN at 24 hours p<0.001 and serum creatinine increased significantly at 48 hours, also study carried by Wacker-Gussmann et al [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] found that cystatin C level and the cystatin C/creatinine ratio independently predict the risk of CIN in patients undergoing coronary angiography, but another study by Ribichini et al [32] found a significant increase in serum cystatin C concentrations 12 hours earlier than serum creatinine, therefore a rise of serum cystatin C at 12 hours from baseline was the earliest predictor of CIN than serum creatinine [18].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In present study was found a highly significant increment in serum creatinine and cystatin C while decrease in eGFR 24 hours after angiography (p<0.001, 0.01) when compared between two groups (CIN+, CIN-). This result is consistent with Wang et al, Liu et al and Nozue et al founded serum level of cystatin C is a reliable marker for CIN at 24 hours p<0.001 and serum creatinine increased significantly at 48 hours, also study carried by Wacker-Gussmann et al [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] found that cystatin C level and the cystatin C/creatinine ratio independently predict the risk of CIN in patients undergoing coronary angiography, but another study by Ribichini et al [32] found a significant increase in serum cystatin C concentrations 12 hours earlier than serum creatinine, therefore a rise of serum cystatin C at 12 hours from baseline was the earliest predictor of CIN than serum creatinine [18].…”
Section: Discussionsupporting
confidence: 91%
“…While Ribichini et al studied 166 patients and he measured their serum creatinine and cystatin C at baseline and at 12, 24 and 48 hours after exposure to contrast media. He found that CIN occurred in 30 patients (18%) [18]. A prospective study of consecutive 87 patients who underwent elective PCI and CAG, 31 patients had a moderate kidney disease, CIN occurred in 18 patients and was more frequent 42.0% [19].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Surprisingly, no additional diagnostic value of cystatin C over serum creatinine in the determination of CIN was observed when Ribichini et al, (2012) [33]; studied the diagnostic accuracy of serum creatinine and cystatin C as early predictors of CIN; they found that serum Cys concentrations did not reach statistically significant differences in the CIN+ vs CIN-groups, including at 48 h, while Serum creatinine in CIN+ patients was significantly higher than in the CIN-group only after 48 h. Moreover, they found that absolute changes in serum creatinine proved more accurate than Cys for predicting CIN at an early stage (12 h after the renal insult). The ∆ serum creatinine at 12 h from baseline was a strong predictor of CIN (AUC = 0.80), while the ∆ Cys at 12 h from baseline was not predictive of CIN (AUC= 0.49).…”
Section: -Fasting Plasma Glucose Level By Colorimetric Methodsmentioning
confidence: 98%
“…Unlike creatinine, production of cystatin C is unaffected by muscle mass or diet, and remains constant even in the presence of intercurrent infection or malignancy [39]. Most [39,[41][42][43][44][45], although not all studies [37,46,47], including a meta-analysis [30], have demonstrated superiority of cystatin C as a measure of GFR in comparison to serum creatinine. However, cystatin C is ubiquitous, and many other factors, including age, male gender, weight, height, smoking and steroid therapy, have been shown to be associated independently with higher serum cystatin C levels after adjustment for renal function, suggesting that it may lack specificity for renal impairment [48,49].…”
Section: Endogenous Filtration Markers A) Creatininementioning
confidence: 99%